Farms and Mines: A Conflicting or Complimentary Land Use Dilemma in Western Australia? - Haslam McKenzie, Fiona M. (Journal for Geography, 2009)
The Western Australian economy has always been underpinned by farming and mining. Over the last five years the economy has experienced phenomenal growth due to unprecedented global demand for resources and increasingly, agricultural land is being given up for mining. Changing land uses challenge industry and community leaders; some communities are overwhelmed by a new population connected with mining, bringing with it a range of social and economic tensions that small communities struggle to cope with. This paper will discuss the conflicting issues regarding land use planning, local and environmental governance and sense of place while also canvassing positive developments that have enhanced community and regional economic development, thus building a resilient future.